The girls from ames eaudiobook A story of women and a forty-year friendship. - Zaslow, Jeffrey (Recorded Books Inc., 2009)
Best-selling author Jeffrey Zaslow is a Will Rogers Humanitarian Award winner and was the replacement advice columnist for Ann Landers in the Chicago Sun-Times. Here he turns his eye to a group of 11 friends who grew up in Ames, Iowa, during the 1960s, a period of unprecedented opportunity for women. What emerges is an inspiring look at the power of friendship to overcome challenges.